Pengaruh Emotional Exhaustion dan Employee Engagement terhadap Turnover Intention dengan Job Satisfaction sebagai Variabel Mediasi: Studi pada Karyawan Generasi Z di Jawa Timur - Salimatus Saadah; Antin Rakhmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of emotional exhaustion and employee engagement on turnover intention, with job satisfaction as a mediating variable among Generation Z employees in East Java. Using the Job Demands-Resources (JD-R) model and Herzberg’s Two-Factor Theory as theoretical frameworks, the research involved 129 respondents collected through purposive sampling. Data were analyzed using path analysis with SPSS 27. The results show that emotional exhaustion has a positive and significant effect on turnover intention, while employee engagement has a negative and significant effect. Job satisfaction is also proven to have a negative effect on turnover intention and mediates the relationship between the independent variables and turnover intention partially. These findings highlight the importance of managing psychological well-being, improving work engagement, and maintaining job satisfaction to reduce employee turnover, especially for Generation Z in the workforce.